Mercury contamination alters soil microbial communities and functional traits in farmland soils of a mining region, south-western China - Yu, Gao; Chen, Fen; Zhang, Xiaodong; Wang, Zuhua (Frontiers in Microbiology, 2025)
IntroductionThis study aimed to determine the status of soil mercury (Hg) contamination and to understand the associated soil microbial community structure and function, along with their relationships with environmental factors, in farmlands surrounding mercury mining regions.MethodsSoil samples were collected from farmland surrounding a mercury mining region (Chuandong town, CD, Huaqiao town, DP, Bahuang town, BG, and Shuangjiang town, LT) in Tong Ren, south-western China. We analyzed soil physicochemical properties, Hg pollution indices, and bacterial community structure and function. The interactions among soil environmental factors and bacterial community structure and function were determined using correlation analysis and redundancy analysis.ResultsThe soils exhibited varying degrees of Hg contamination: CD and LT soils were categorized by “light” Hg contamination, whereas DP and BG soils exhibited “moderate” Hg contamination. The potential ecological risk was “moderate” for CD soils, “considerable” for BG and LT soils, and “high” for DP soils. Long-term Hg contamination significantly increased soil bacterial community diversity and decreased bacterial community richness. Bacterial communities underwent adaptive restructuring, with Acidobacteria (16.90% relative abundance) dominating the acidic, high-Hg soils at the DP site and Proteobacteria (29.71% relative abundance) thriving in nutrient-rich conditions at the LT site. Key metal-resistant genera (Rokubacteriales, Gaiella) emerged as potential biomarkers of contamination. PICRUSt2 analysis revealed maintained metabolism potential under Hg stress, with carbohydrate metabolism and amino acid metabolism pathways collectively accounting for 26.43% of all predicted functions. Redundancy analysis identified soil pH, THg, and Gaiella were the key the factors driving the soil bacterial community function, with their independent contributions contributions to the variance being 72.83, 84.64, and 81.97%, respectively.DiscussionThese findings provide a mechanistic understanding of microbial resilience in Hg-contaminated ecosystems and identify critical leverage points for remediation strategies targeting both metal toxicity and the functional restoration of agricultural soils.